Conceptualising the social world : principles of sociological analysis - Scott, John , 1949- (Cambridge University Press, 2011)
"This comprehensive and authoritative statement of fundamental principles of sociological analysis integrates approaches that are often seen as mutually exclusive. John Scott argues that theorising in sociology and other social sciences is characterised by the application of eight key principles of sociological analysis: culture, nature, system, structure, action, space-time, mind and development. He considers the principal contributions to the study of each of these dimensions in their historical sequence in order to bring out the cumulative character of knowledge. Showing that the various principles can be combined in a single disciplinary framework, Scott argues that sociologists can work most productively within an intellectual division of labour that transcends artificial theoretical and disciplinary differences. Sociology provides the central ideas for conceptualising the social, but it must co-exist productively with other social science disciplines and disciplinary areas"